2022
DOI: 10.3390/ijerph19063236
|View full text |Cite
|
Sign up to set email alerts
|

The Well-Being of the German Adult Population Measured with the WHO-5 over Different Phases of the COVID-19 Pandemic: An Analysis within the COVID-19 Snapshot Monitoring Study (COSMO)

Abstract: The aim of this study is to evaluate factors associated with the subjective well-being (SWB) and suspected depression measured with WHO-5 among German adults during different phases of the COVID-19 pandemic. Survey data were analyzed from the COVID-19 Snapshot Monitoring (COSMO) study, which collected data from 972, 1013, and 973 participants in time point 1 (19–20 May 2020), time point 2 (15–16 September 2020), and time point 3 (21–22 December 2020), respectively. Descriptive analyses and logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
6
8
0
Order By: Relevance
“…Declines in mental health from the second wave onward in the general population While most studies on mental health in the COVID-19 pandemic in Germany examine its first months only (43), our results shed light on the development of symptoms of depression in the adult population until June 2022 and reveal two increases. Consistent with our finding of increased mean depressive symptom scores as well as positive screens between the last months of 2020 and spring 2021, i.e., during the second wave of infections, a German study reports lower subjective psychological wellbeing measured using a screening tool for depression in December 2020 compared to May and September 2020 (116). Also in keeping with our findings, a representative survey of the German resident adult population showed that a far larger percentage of the population found the overall situation "depressing" in the second lockdown than in the first (47).…”
Section: Reduction In Symptoms Of Depression In the First Phases Of T...supporting
confidence: 90%
“…Declines in mental health from the second wave onward in the general population While most studies on mental health in the COVID-19 pandemic in Germany examine its first months only (43), our results shed light on the development of symptoms of depression in the adult population until June 2022 and reveal two increases. Consistent with our finding of increased mean depressive symptom scores as well as positive screens between the last months of 2020 and spring 2021, i.e., during the second wave of infections, a German study reports lower subjective psychological wellbeing measured using a screening tool for depression in December 2020 compared to May and September 2020 (116). Also in keeping with our findings, a representative survey of the German resident adult population showed that a far larger percentage of the population found the overall situation "depressing" in the second lockdown than in the first (47).…”
Section: Reduction In Symptoms Of Depression In the First Phases Of T...supporting
confidence: 90%
“…65,66 Younger employees also had lower odds of psychological wellness, and literature points to some possible predictors: their exposure to the media for a longer period, which is associated with increased COVID-related anxiety, the closure of recreational facilities, and future uncertainties. 62,65 This study also indicates that those employees who only worked from home during the pandemic had lower psychological well-being, replicating what had been found by Xiao et al 68 and Ogata et al 60 Gaspar et al 67 offer some plausible explanations for decreased well-being among those WFW: individuals were confined to their homes, with less or no opportunity to socialize, sedentarism, obscure work-life boundaries, and long hours of screen exposure. Regarding this last factor, overexposure to COVID-19 information has been associated with emotional distress.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with our finding of increased mean depressive symptom scores as well as positive screens between the last months of 2020 and spring 2021, i.e. during the second wave of infections, a German study reports lower subjective psychological well-being measured using a screening tool for depression in December 2020 compared to May and September 2020 (106). Also in keeping with our findings, a representative survey of the German resident adult population showed that a far larger percentage of the population found the overall situation "depressing" in the second lockdown than in the first (39).…”
Section: Declines In Mental Health From the Second Wave Onward In The...supporting
confidence: 90%